WHY EYSENCK DID NOT TALK ABOUT HEALTH PSYCHOLOGY - Ibáñez Guerra, Elena (Anales de Psicología / Annals of Psychology)
In this study, it is tried to prove that the work of Eysenck is centred in the topic of the health from its beginnings. The mental health served him as approach for the establishment of its trifactorial personality model. Later, he tries to apply this model to the field of the psychooncology, seeking to establish relationships between Personality and Cancer. Both of them perspectives eysenckianas exemplify the existence of the two dominant paradigms that they are at the present on the concept of Health.